Skincare Overclaim Crisis Communication in Restoring Cosmetic Manufacturer Image - Indra Gozali; Lasmery RM Girsang (International Journal Labs, 2026)
This study analyzes crisis communication management in the brand image recovery of cosmetics manufacturing companies after the skincare overclaim issue. The focus of the research is directed at the experiences of five brand owners as business customers affected by the perception crisis, as well as on the Public Relations function carried out by sales because the company does not have a formal PR department. The research used a qualitative approach of case studies with semi-structured interviews, documentation, and thematic analysis. The results of the study show that the issue of overclaims is not only understood as a problem of promotional claims, but also as a crisis of trust that shakes procedural credibility, information integrity, institutional responsibility, and brand owner security. Sales is considered responsive and empathetic, but the initial response is still too dependent on personal abilities so it is not fully supported by a documented crisis communication system. Image restoration begins to take shape through dialogue, follow-up, claims revision, and company openness, but long-term recovery requires claim approval workflow, claim substantiation file, crisis communication SOP, escalation flow, brand owner education, and sales training as crisis communication frontliners. This article confirms that the restoration of the brand image of cosmetics manufacturing in B2B relations must combine empathic communication with transparent, consistent, and accountable claims governance.